2018
DOI: 10.1080/15563650.2018.1478425
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in the treatment of acute overdose in the emergency department

Abstract: Blacks and Hispanics are significantly less likely to receive any antidote when presenting to the ED for acute drug overdose. Further studies are needed to determine national prevalence of this apparent disparity in care and to fully characterize how race plays a role in management of acute overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Moreover, treatment differences contribute significantly to disparities in overdose mortality. Compared to white patients, black and Hispanic patients are significantly less likely to receive antidotes for acute overdose when presenting to the emergency department 52. Thus, researchers highlight the importance of more extensive and comprehensive research being performed regarding the connection between social determinants and opioid use and the most appropriate method for training providers on treatment options 22.…”
Section: Key Findings For Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, treatment differences contribute significantly to disparities in overdose mortality. Compared to white patients, black and Hispanic patients are significantly less likely to receive antidotes for acute overdose when presenting to the emergency department 52. Thus, researchers highlight the importance of more extensive and comprehensive research being performed regarding the connection between social determinants and opioid use and the most appropriate method for training providers on treatment options 22.…”
Section: Key Findings For Reviewsmentioning
confidence: 99%
“…In the 1990s, rates of overdose deaths in New York City were consistently higher among blacks/African-Americans and Hispanics/Latinos compared to whites,57 while our analysis showed higher mortality rates among whites than blacks and Hispanics nationally during 2002-2017 2. Disparities in overdose mortality may be related to differences in treatment, as Wilder et al found that compared to white patients, black and Hispanic patients are significantly less likely to receive antidotes for acute overdose when presenting to the emergency department 52. Thus, instead of simply reducing opioid prescribing, policymakers addressing the opioid epidemic should focus on upstream structural factors, including economic opportunity, social cohesion, racial disadvantage, and life satisfaction 24…”
Section: Summary Conclusion and Global Health Implicationsmentioning
confidence: 99%
“…On a related note, our group recently published the first data [1] in the toxicology literature that used race as an independent predictor variable for treatment. We found that both non-Hispanic Black and Hispanic patients were less likely to receive any antidote when presenting with acute drug overdose.…”
mentioning
confidence: 99%